Endothelial Lipase Is Involved in Cold-Induced High-Density Lipoprotein Turnover and Reverse Cholesterol Transport in Mice - Schaltenberg, Nicola; John, Clara; Heine, Markus; Haumann, Friederike; Rinninger, Franz; Scheja, Ludger; Heeren, Joerg; Worthmann, Anna (Frontiers in Cardiovascular Medicine, 2021)
The physiologic activation of thermogenic brown and white adipose tissues (BAT/WAT) by cold exposure triggers heat production by adaptive thermogenesis, a process known to ameliorate hyperlipidemia and protect from atherosclerosis. Mechanistically, it has been shown that thermogenic activation increases lipoprotein lipase (LPL)-dependent hydrolysis of triglyceride-rich lipoproteins (TRL) and accelerates the generation of cholesterol-enriched remnants and high-density lipoprotein (HDL), which promote cholesterol flux from the periphery to the liver. HDL are also subjected to hydrolysis by endothelial lipase (EL) (encoded by LIPG). Genome-wide association studies have identified various variants of EL that are associated with altered HDL cholesterol levels. However, a potential role of EL in BAT-mediated HDL metabolism has not been investigated so far. In the present study, we show that in mice, cold-stimulated activation of thermogenic adipocytes induced expression of Lipg in BAT and WAT but that loss of Lipg did not affect gene expression of thermogenic markers. Furthermore, in both wild type (WT) and Lipg-deficient mice, activation of thermogenesis resulted in a decline of HDL cholesterol levels. However cold-induced remodeling of the HDL lipid composition was different between WT) and Lipg-deficient mice. Notably, radioactive tracer studies with double-labeled HDL indicated that cold-induced hepatic HDL cholesterol clearance was lower in Lipg-deficient mice. Moreover, this reduced clearance was associated with impaired macrophage-to-feces cholesterol transport. Overall, these data indicate that EL is a determinant of HDL lipid composition, cholesterol flux and HDL turnover on conditions of high thermogenic activity.